Is my patient too sad to approach their fear? Depression severity and imaginal exposure outcomes for patients with OCD. (March 2021) - Berman, Noah Chase; Hezel, Dianne M.; Wilhelm, Sabine
Abstract: Background and objectives: There is conflicting research on how comorbid depression impacts the treatment of obsessive compulsive disorder (OCD) with exposure with response prevention. To better understand this relationship, the current study tests theoretical claims that greater depression limits motivation to engage in exposures, restricts habituation, and interferes with adaptive learning. Methods: Fifty-one individuals with OCD completed a diagnostic interview and self-report questionnaires assessing depression symptom severity and then participated in a standardized imaginal exposure protocol, in which they repeatedly approached an idiosyncratic fear deemed "moderately anxiety-provoking." Results: Contrary to expectations, linear regression models indicated that depression symptom severity was not independently associated with motivation, subjective or objective within-session habituation or adaptive learning outcomes. However, the perceived likelihood of the best-case scenario occurring as a result of the exposure moderated the relationship between depression severity and motivation to engage in the exposure exercise. Limitations: Use of a one-session exposure protocol precludes conclusions regarding how depression is associated with outcomes in a full ERP treatment. Conclusions: Depression symptom severity was not independently associated with motivation, habituation, or adaptive learning. The observed non-significant effects suggest that degree of depression, on its own, is not a meaningful indicator of how patients with OCD will fare an exposure intervention. Highlights: The relationship between depression and OCD treatment response is conflicted. Over fifty individuals with OCD completed a standardized imaginal exposure paradigm. Depression severity was not independently associated with key exposure variables. Appraisals of exposure moderated relationship between depression and motivation. Exposure therapy for OCD may not be directly impacted by depression severity.